Characterisation of inflorescence development in Zea mays with four developmental mutants : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Science at Massey University, Palmerston North, New Zealand - Brown, Murray (Massey University, 2000)
The genetic control of inflorescence development has been studied in great detail in the model dicotyledonous plants Arabidopsis thaliana and Antirrhinum majus. In contrast, little is known about the genetic regulation in monocotyledonous species. Using maize (Zea mays) as a model system, the phenotypes were documented for the branched silkless1 (bd1) and ramosa (ra1, ra2, and ra3) inflorescence mutants that are characterised by abnormally branched ears. A comparison of the adult morphology and developing inflorescences using scanning electron microscopy in mutant and normal maize reveals that there are at least five reproductive meristems that can be identified in maize: the inflorescence meristem, the branch meristem, the spikelet pair meristem, the spikelet meristem, and the floret meristem. The abnormal branching in bd1 and the three-ramosa mutations is the result of the failure to determine the fate of specific types of reproductive meristems in both tassels and ears. Both RA1 and RA3 are required for the determination of spikelet pair development in branch primordia. RA2 is necessary for determinate growth in spikelet pair meristems. BD1 is required determinate growth of spikelet meristems by specifying a determinate floral meristem identity. The classification of the different types of reproductive meristems and the genes that regulate their development is essential to understanding the genetic programs that underlie inflorescence morphogenesis in maize and other Gramineae.
Keywords: Corn -- Flowering; Inflorescences -- Genetics; Flowers -- Morphogenesis